2020
DOI: 10.31331/medivesveteran.v4i1.1010
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Stuktur Aljabar dengan Penemuan Terbimbing untuk Meningkatkan Kemampuan Abstraksi dan Menulis Bukti Matematika

Abstract: Penelitian ini merupakan penelitian pengembangan dengan menggunakan model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation). Penelitian ini bertujuan untuk mendapatkan bahan ajar dengan penemuan terbimbing yang sarat dengan konstruksi pemahaman aljabar abstrak dengan pertanyaan-pertanyaan penggiring dan strategi bantuan sebelum diberikannya definsi atau dibuktikannya teorema. Pada tahap analisis peneliti mengidentifikasi dan merumuskan masalah. Pada tahap desain, peneliti membuat r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…The results of this study support the results of research conducted by Ratih Kusumawati & Prihadi Kurniawan who concluded that the development of teaching materials with guided discovery can effectively improve abstraction abilities (Kusumawati & Kurniawan, 2020). When viewed from the scenario in inquiry-based learning, learning activities begin with activities to formulate problems, develop hypotheses, collect evidence, test hypotheses, draw and test temporary conclusions and write conclusions (Fahyuni, 2016).…”
Section: Posttest Data Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study support the results of research conducted by Ratih Kusumawati & Prihadi Kurniawan who concluded that the development of teaching materials with guided discovery can effectively improve abstraction abilities (Kusumawati & Kurniawan, 2020). When viewed from the scenario in inquiry-based learning, learning activities begin with activities to formulate problems, develop hypotheses, collect evidence, test hypotheses, draw and test temporary conclusions and write conclusions (Fahyuni, 2016).…”
Section: Posttest Data Analysissupporting
confidence: 82%
“…The development of teaching materials with guided discovery can effectively improve abstraction skills (Kusumawati & Kurniawan, 2020). However, there has been no research that has examined the effect of inquiry learning on self-efficacy and abstraction ability at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this research are supported by several previous studies related to mathematical proofbased teaching materials. These include the use of teaching materials on the ability to write evidence (Kusumawati & Kurniawan, 2020), Nur'afni et al (2019 regarding proof-based binomial teaching materials, and the application of student worksheet design for learning proof systems (Huwaa & Matitaputty, 2019) produces valid, practical, and effective teaching materials and student worksheets.…”
Section: Discussionmentioning
confidence: 99%
“…Nurhasanah mengungkapkan bahwa indikator kemampuan abstraksi matematis memiliki lima indikator yaitu merepresentasikan kasus ke dalam kaidah dan simbol-simbol matematika, pengidentifikasian dan merumuskan kasus, penyusunan objek matematika lebih lanjut, penyusunan teori matematika terkait teori lain, dan proses mengoperasikan simbol (Kusumawati & Kurniawan, 2020).…”
Section: Pendahuluanunclassified